2020
DOI: 10.1016/j.soildyn.2020.106200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the variability of soil profile properties on weak and strong seismic response

Abstract: Characterizing the potential effect of local site conditions on the amplification of ground motions is a critical aspect of seismic hazard and risk assessment. The aim of this study is to investigate the reliability and the limit of using the average shear wave velocity in the upper 30 m of the soil profile ,30 s v , as single proxy, to characterize seismic site effects for weak and strong events.To this regard, a dataset of 300 one-dimensional soil profiles with a given ,30are generated through a Monte Carlo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the article [2], for the stochastic study of seismic risk, the variability of the V s was considered, and in [5], the effects resulting from the choice of three different ways of considering the V s were discussed. In [6], the Monte Carlo method was applied. The parameters that substantially influence the surface seismic amplification depend on the deformation in a non-linear way [7] (among many others).…”
Section: Introductionmentioning
confidence: 99%
“…In the article [2], for the stochastic study of seismic risk, the variability of the V s was considered, and in [5], the effects resulting from the choice of three different ways of considering the V s were discussed. In [6], the Monte Carlo method was applied. The parameters that substantially influence the surface seismic amplification depend on the deformation in a non-linear way [7] (among many others).…”
Section: Introductionmentioning
confidence: 99%
“…Ground response analysis is a key tool in seismic hazard assessment, as the reference ground motion (i.e., at the outcropping bedrock with a flat surface) can be different from that recorded at a nearby site in terms of frequency content, amplitude, duration and polarisation due to local topographic and stratigraphic conditions (e.g., [1]). Previous seismic site response investigations have focused on: (i) the heterogeneity of the deposit with depth and the soil nonlinearity (e.g., [2][3][4][5][6][7]), (ii) the variability of the soil mechanical properties and input motion characteristics (e.g., [8][9][10][11][12][13][14][15][16][17]), (iii) the ground surface topography (e.g., [18][19][20][21][22][23][24][25][26][27]), (iv) the buried morphologies (e.g., [28][29][30]) and (v) the numerical code and approach employed in the simulations (e.g., [31][32][33][34][35][36][37][38]).…”
Section: Introductionmentioning
confidence: 99%
“…Gobbi et al [19] performed 1D simulation of site response analysis with a set of 40 earthquake records for stochastically generated horizontally layered soil profiles. They concluded that amplification factors are best predicted as a function of V s30 in conjunction with the dominant period of the site and the shear wave velocity gradient.…”
Section: Introductionmentioning
confidence: 99%